Development and productivity of soybean sown in the off-season - Kolesny, Vitor; Pimentel, João Roberto; Szareski, Vinícius Jardel; Souza, Velci Queiróz de; Aumonde, Tiago Zanatta; Pedó, Tiago (Scientia Agraria Paranaensis, 2022)
The objective of this work was to evaluate the influence of different sowing times on plant height and yield of soybean seeds produced in two consecutive years and in two seasons in the off-season period. The experiment was carried out in an open field, at the Federal University of Pelotas, in the municipality of Capão do Leão, RS. The experimental design was completely randomized. In order to evaluate growth attributes and yield characters, the plant height, number of pods, seeds per plant, seed production, number of seeds per pod. Sowing at different times of the off-season affects in a different way the production of soybean seeds. Sowing at the end of February negatively affects plant height and soybean seed production in relation to sowing in early January.